Systematic Review and Meta-analysis of Randomized Controlled Trials on Manual Therapy for the Treatment of Gastroesophageal Reflux Disease - Mengdie Yan; Yunzhou Shi; Yanqin Liu; Yue Shi; Mengzhu Zhang; Dongnan Chen; Senlin Ye; Shiyin Li; Yue Feng (Chinese Medicine and Natural Products, 2023)
Objective The objective of our study was to systematically evaluate the clinical efficacy and safety of manual therapy in the treatment of gastroesophageal reflux disease (GERD), providing a reference value for clinical decision-making.